P145 Inflammatory Bowel Disease patients requiring surgery can be treated in referral centres regardless of the COVID-19 status of the hospital: results of a multicentric European study during the first COVID-19 outbreak (COVIBD-Surg). (27th May 2021) - Rottoli, M; Pellino, G; Tanzanu, M; Baldi, C; Frontali, A; Carvello, M; Foppa, C; Kontovounisios, C; Tekkis, P; Colombo, F; Sancho-Muriel, J; Matteo, F; et al.
Abstract: Background: Little is known regarding the outcomes of inflammatory bowel disease (IBD) patients who required surgery during the outbreak of Coronavirus disease 19 (COVID-19). This study aimed to compare outcomes of IBD patients undergoing surgery in COVID-19-treatment and COVID-19-free hospitals. Methods: Retrospective study involving patients undergoing IBD surgery in seven centres (six COVID-19-treatment hubs and one COVID-free hospital) across 5 European countries during the period of highest reduction of elective activity due to the first peak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections. Predictive variables of the risk of moderate-to-severe postoperative complications were analysed using logistic regression analysis. Considering the large number of regressors and the risk of over-fitting due to the small number of events, the least absolute shrinkage and selection operator (LASSO) method was used. Results: Of the 91 patients (59 males, 64.8%) with Crohn's disease (54, 59.3%) or ulcerative colitis (37, 40.7%), 66 (72.5%) had surgery in a COVID-19-treatment hospital, while 25 (27.5%) were treated in the COVID-19-free centre. A higher proportion of COVID-19-treatment patients required urgent surgery (48.4% vs 24%, p=0.035), did not discontinue the biologic therapy (15.1% vs. 0%, p=0.039), underwent surgery without a SARS-CoV-2 test (19.7% vs. 0%, p=0.0033), and were admitted to intensive care postoperatively (10.6% vs. 0%, p=0.032). Three patients (4.6%) of the COVID-19-treatment group had a SARS-CoV-2 infection during the hospital course. Use of steroids at surgery (Odds ratio [OR]=4.10, 95% CI 1.14–15.3, p=0.03), presence of comorbidities (OR=3.33, 95% CI 1.08–11, p=0.035), and Crohn's disease (vs. ulcerative colitis, OR=3.82, 95% CI 1.14–15.4, p=0.028) were associated with risk of moderate-to-severe postoperative complications. The admission to a COVID-19-treatment hospital was not associated with higher risks of complications (OR 2.06, 95% CI 0.54–10.4, p=0.30) Conclusion: Although a SARS-CoV-2 infection in the postoperative period represented a concrete risk in IBD patients undergoing surgery in COVID-19-treatment hospitals, the study showed that IBD patients can undergo surgery regardless of the COVID-19-status of the referral centre. The study also showed the lack of standardized practice for IBD patients requiring surgery during the COVID-19 outbreak.